2011
DOI: 10.4103/1658-354x.76480
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the outcome of cesarean section for women with severe pre-eclampsia in a third world setting

Abstract: Objective:To compare the outcome of subarachnoid block (spinal anesthesia) and general anesthesia in Cesarean delivery for women with severe pre-eclampsia.Methods:A retrospective study of women with severe pre-eclampsia requiring Cesarean section from January 2005 to June 2009 was carried out. Maternal age, parity, gestational age at delivery, booking status, Apgar scores, maternal and perinatal mortality of the sub-arachnoid block group were compared with those of general anesthesia group using χ2, Student t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Considering the neonatal outcomes after various anesthesia techniques in cesarean delivery among preeclamptic patients, no statistically significant difference was found in the one- and five-minute Apgar scores and the umbilical artery blood gas markers between the two groups of patients receiving spinal or general anesthesia ( 25 ). Other studies in support of subarachnoid block have also shown that transient neonatal depression and birth asphyxia are more common among preeclamptic women who have received general anesthesia ( 26 ). Comparing umbilical arterial fetal base deficit and other markers of maternal and neonatal well-being in 70 preeclamptic patients undergoing cesarean delivery who were randomized into groups receiving either spinal or general anesthesia, the spinal group had a higher mean umbilical arterial base deficit and a lower median umbilical arterial pH, but other markers of a compromised neonatal condition, including the requirement for neonatal resuscitation, an Apgar score < 7, an umbilical arterial pH < 7.2, and the need for neonatal intermittent positive pressure ventilation were the same among the two groups ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the neonatal outcomes after various anesthesia techniques in cesarean delivery among preeclamptic patients, no statistically significant difference was found in the one- and five-minute Apgar scores and the umbilical artery blood gas markers between the two groups of patients receiving spinal or general anesthesia ( 25 ). Other studies in support of subarachnoid block have also shown that transient neonatal depression and birth asphyxia are more common among preeclamptic women who have received general anesthesia ( 26 ). Comparing umbilical arterial fetal base deficit and other markers of maternal and neonatal well-being in 70 preeclamptic patients undergoing cesarean delivery who were randomized into groups receiving either spinal or general anesthesia, the spinal group had a higher mean umbilical arterial base deficit and a lower median umbilical arterial pH, but other markers of a compromised neonatal condition, including the requirement for neonatal resuscitation, an Apgar score < 7, an umbilical arterial pH < 7.2, and the need for neonatal intermittent positive pressure ventilation were the same among the two groups ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a history of pre-eclampsia were 2.5 times more likely to have cesarean delivery (OR = 2.5; p<0.02) [ 19 ]. It is possible that cases of stillbirths and maternal mortality associated with CS could be also associated to preeclampsia [ 20 ]. Robson in 2013 suggested that satisfactory CS rate in the group 1 would be around 10% and in that for Group 3, the caesarean section rate should be no higher than 3%.…”
Section: Discussionmentioning
confidence: 99%
“…This study found no significant differences in Apgar score (1 min) and Apgar score (5 min) for the morbid obesity group compared with non-obese patients. Ajuzieogu et al [ 14 ] and Moodley et al [ 15 ] found similar neonatal outcomes irrespective of anesthesia administered; in addition, Ajuzieogu et al [ 14 ] showed that maternal mortality rates are similar after spinal and GA modes. GA should be preferred, as well as spinal anesthesia combined with epidural anesthesia, which has quick onset with very short time of fetus disengagement and high Apgar score.…”
Section: Discussionmentioning
confidence: 99%